2013
DOI: 10.1038/nchem.1765
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer cell membrane assembly

Abstract: Eukaryotic subcellular membrane systems, such as the nuclear envelope or endoplasmic reticulum, present a rich array of architecturally and compositionally complex supramolecular targets that are yet inaccessible. Here we describe layer-by-layer phospholipid membrane assembly on microfluidic droplets, a route to structures with defined compositional asymmetry and lamellarity. Starting with phospholipid-stabilized water-in-oil droplets trapped in a static droplet array, lipid monolayer deposition proceeds as oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 31 publications
2
141
0
2
Order By: Relevance
“…These strategies have focused on developing automated, programable and controlled delivery systems for the assembly of liposomes of controllable physicochemical characteristics using microfluidic technology, which has emerged as a robust alternative for the assembly of vesicles that reigns in some of the weaknesses associated with traditional liposome assembly methods. In addition to this, it is important to mention that microfluidics has been recognized as an enabling new technology providing a controlled environment to address issues of size and structure heterogeneity (Matosevic, 2012;Matosevic & Paegel, 2013). Recently, a number of microfluidic approaches have been described aimed at circumventing some of the main drawbacks encountered with traditional lipid assembly techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies have focused on developing automated, programable and controlled delivery systems for the assembly of liposomes of controllable physicochemical characteristics using microfluidic technology, which has emerged as a robust alternative for the assembly of vesicles that reigns in some of the weaknesses associated with traditional liposome assembly methods. In addition to this, it is important to mention that microfluidics has been recognized as an enabling new technology providing a controlled environment to address issues of size and structure heterogeneity (Matosevic, 2012;Matosevic & Paegel, 2013). Recently, a number of microfluidic approaches have been described aimed at circumventing some of the main drawbacks encountered with traditional lipid assembly techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, one could entrap a biochemical pathway inside liposomes and check whether the tested chemical interferes with it, and how. The recent advent of special methods for producing solute-filled liposomes (in a controlled manner), with or without the help of microfluidic devices, allows a high-throughput liposome production, and consequently the construction of "liposome arrays" [33,34]. The unique cell-like microenvironment of the synthetic cells can be used for screening and evolving biological parts like nucleic acids, proteins, and especially membrane proteins-as evidenced by recent strategies ("liposome display" [35]).…”
Section: Biotechnologymentioning
confidence: 99%
“…In 2003, Pautot et al developed a method for systematically engineering vesicles with asymmetric bilayers where each leaflet was assembled independently [50]; in 2011, Matosevic et al presented an assembly-line strategy able to achieve a completely parametrized and reproducible phospholipid vesicle generation [51]. Later on, the same authors [47] demonstrated the formation and subsequent (phospholipid) stabilization of droplets using a flow focusing device. After a defined delay, droplets could be trapped within pockets and the continuous phase gradually exchanged with a secondary phase containing a different type of phospholipid that deposits on the previously formed bilayer.…”
Section: Artificial Cells Based On Liposomesmentioning
confidence: 99%